The First In-Depth Assessment Of Carbon Capture Utilization And Sequestration (Ccus) For Co2 Management Of South Sumatera Sng Plant - Utomo P Iskandar (Testing Center for Oil and Gas LEMIGAS, 2013)
A commercial low-rank coal SNG (substitute natural gas) plant is being planned to build in Pendopo, South Sumatra. However, the CO2 produced is not allowed to be vented and should be managed properly. One approach to manage this anthropogenic CO2 emission is through the utilization for CO2 EOR (enhanced oil recovery) or CO2 sequestration. This workaims to investigate the possibility of application and the readiness carbon capture utilization and sequestration (CCUS) for CO2 management of South Sumatera SNG Plant. It presents technical ranking of suitable reservoirs, injection profiles determination, cluster principle of oil fields that can accommodate the amount of CO2 supplied for a number of years, and planning and realization of trunk pipelines and the possibility to reuse the major part of the present infrastructure. The results show the A1 oil field has the highest rank in the sink scoring indicating that this field has highest suitability for CO2 EOR application and CO2 sequestration. Three clusters are formed, north, southeast and west cluster as the basis to establish pipelines network development. The largest CO2 storage potential is in southeast cluster, 27 MtCO2 and the injection strategy developed is successful to manage CO2 supply from SNG Plant.